KONFLIK SOSIAL PROYEK KILANG MINYAK GRASS ROOT REFINERY (GRR) DENGAN WARGA DESA SUMURGENENG KABUPATEN TUBAN - Pratiwi, Ni Komang Rahma Tri (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
In the process of building the Root Grass Refinery (GRR) oil refinery project in Sumurgeng Village, Tuban Regency, East Java, there was rejection from landowners by considering the environmental impact that could increase because there were already companies that were also engaged in the oil and gas sector and steam energy located quite close to Sumurgeneng Village. This research aims to analyze how social conflict resolution occurs based on Lewis Alfred Coser's conflict theory. This research uses a qualitative method with a descriptive approach and data collection techniques in the form of observation, interviews and documentation studies. The results of this study indicate that the conflict that occurred in Sumurgeneng Village was a realistic conflict and also strengthened solidarity of Sumurgeneng Village residents to defend their land rights which was reflected in the resistance actions carried out. Furthermore, as safety valve, PT Pertamina-Rosneft conducted various corporate social responsibility (CSR) programs. Keywords: Social conflict, oil refinery, Lewis A. Coser conflict theory